2020
DOI: 10.3390/ijerph17030921
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Job Satisfaction and Burnout Levels of Emergency Department Professionals during a Period of Economic Recession

Abstract: Satisfaction at work has been found to be a predictive factor of permanency. On the other hand, burnout has been associated with financial loss. The purpose of this study was to analyse the levels of satisfaction and burnout of professionals in a hospital emergency department and make a comparison with results from the same service during the economic recession in 2012. An analytical, cross-sectional and descriptive study was undertaken during two time periods into the levels of satisfaction and burnout of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
2
14
0
1
Order By: Relevance
“…satisfaction is a predictor of burnout. Results of the in-depth interviews confirm those studies showing that job satisfaction causes burnout syndromes by healthcare workers [21], and not vice versa [23].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…satisfaction is a predictor of burnout. Results of the in-depth interviews confirm those studies showing that job satisfaction causes burnout syndromes by healthcare workers [21], and not vice versa [23].…”
Section: Discussionsupporting
confidence: 83%
“…Annual income and household economic-well-being had a positive association with job satisfaction among healthcare workers in nursing homes [20]. Many studies have shown a negative relationship between job satisfaction and the burnout syndrome of nurses and doctors in a hospital environment from two perspectives: causes and consequences [20,21]. For example, a Turkish study on 250 emergency department professionals in two hospitals found out that a significant relationship exists between burnout and job satisfaction: emotional exhaustion was a significant predictor of all three dimensions of job satisfaction, while depersonalization had no significant effect on job satisfaction [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Coomber and Barriball [ 26 ], an examination of the sources of job dissatisfaction over time has revealed that the most important factors for the stability of nurses are still the work environment and not individual or demographic factors. Many studies have examined and confirmed the relationship between nurses’ job satisfaction and the quality of healthcare perceived by patients [ 7 , 19 , 20 , 31 ], as well as nurses’ retention [ 26 , 38 , 41 , 43 ] and their burnout [ 24 , 44 ]. In accordance with Kalisch [ 13 ], we assume that higher job satisfaction of nurses will result in cost savings, because high JS is associated with lower turnover [ 25 , 45 , 46 ].…”
Section: Overview Of Researchmentioning
confidence: 99%
“…The primary purpose of this research is to investigate the relationships between the independent variable (training program conducted) and dependent variables job performance (Mahmood et al, 2018;Swaminathan et al, 2019;Gridwichai et al, 2020;Alnawfleh, 2020) and job satisfaction (Cascio, 1995;Latif, 2012;Imran & Tanveer, 2015;Ahmed et al, 2016;Sri Dhurgah et al, 2018;Cherif, 2020;Fontova-Almato et al, 2020). This research can be very beneficial for academics as well as managers who anticipate providing training to employees to get them ready to face the challenges that are present in the business environment especially after the lockdown is ended due to the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%